An ancestral luciferase in the Malpighi tubules of a non-bioluminescent beetle! - Viviani, V. R.; Prado, R. A.; Arnoldi, F. C. G. [UNESP]; Abdalla, Fábio Camargo [UNESP] (Royal Soc Chemistry, 2009)
The evolutionary origin of beetle bioluminescence is enigmatic. Previously, weak luciferase activity was found in the non-bioluminescent larvae of Tenebrio molitor (Coleoptera: Tenebrionidae), but the detailed tissular origin and identity of the luciferase-like enzyme remained unknown. Using a closely related giant mealworm, Zophobas morio, here we show that the luciferase-like enzyme is located in the Malpighi tubules. cDNA cloning of this luciferase like enzyme, showed that it is a short AMP-ligase with weak luciferase activity which diverged long ago from beetle luciferases. The results indicate that the potential for bioluminescence in AMP-ligases is very ancient and provide a first reasonable protoluciferase model to investigate the origin and evolution of beetle luciferases.